Remote Interpreting: Issues of Multi-Sensory Integration in a Multilingual Task - Moser-Mercer, Barbara (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractThis article seeks to present evidence for the pivotal role of multi-sensory integration in simultaneous interpreting. The lack of virtual presence has emerged as one of the major factors determining poorer performance in remote as opposed to live simultaneous interpreting. This deterioration of quality appears to be based in early onset of fatigue, which in turn seems to be a consequence of allocating additional cognitive resources to comprehension processes during simultaneous interpreting and therefore depriving other parts of the process, notably production, of the resources necessary to maintain a high level of performance during normal turn time.